Hubungan antara kecerdasan emosi dan personaliti “Big Five” dalam kalangan guru sekolah rendah daerah Kota Tinggi - Ang, Enoch (2017)
The aim of this study was to identify the relationship between emotional intelligence and personality "Big Five" at primary school teachers in Kota Tinggi, Johor. This study involved 250 primary schools teacher in Kota Tinggi. Emotional intelligence was measured using the instrument “Emotional Competence Inventory (ECI)” developed by Richard Boyatzis and Daniel Goleman (1998) which has been translated by Nurzawani (2014). While the teachers' personality was measured using the instrument of the Big Five Personality Inventory (BFI) developed by John, Donahue and Kentle (1991) and has been translated by Janet Ho Siew Ching (2006). Descriptive statistics and inferential statistics in term of t-test and Pearson Correlation Coefficient were used to test hypotheses at the significance level 0.05. The findings of this study shown that the most dominant for primary schools teacher in Kota Tinggi of personality “Big Five” is Conscientiousness, while the teacher’s emotional intelligence is at a high level. There was no significant difference of each dimension of personality “Big Five” based on gender. Results of the study also showed that each dimension of personality “Big Five” (Openness to experience, Conscietiousness, Extraversion, Agreeableness and Neuroticism) was found to have a significant relationship with teacher’s emotional intelligence.